1989
DOI: 10.1083/jcb.108.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis from coated pits of Shiga toxin: a glycolipid-binding protein from Shigella dysenteriae 1.

Abstract: Abstract. Evidence is presented that endocytosis is involved in the transport to the cytosol of the cytotoxin from Shigella dysenteriae 1, Shiga toxin, which acts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
150
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(168 citation statements)
references
References 48 publications
17
150
0
1
Order By: Relevance
“…Using Shiga toxin coupled to horse radish peroxidase, it has been shown that an important fraction of this protein is transported to lysosomes (41,42). We have observed in our experiments a fragment that may correspond to a degradation product of B-Glyc-KDEL (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Using Shiga toxin coupled to horse radish peroxidase, it has been shown that an important fraction of this protein is transported to lysosomes (41,42). We have observed in our experiments a fragment that may correspond to a degradation product of B-Glyc-KDEL (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…At this time, some B-Glyc-KDEL was already detectable in the ER (not shown). The presence of B-Glyc-KDEL in coated pits and vesicles suggests that the protein entered the cells through the clathrindependent pathway, as documented previously for Shiga toxin (41,42). After 2 h at 37°C, the ER became heavily labeled (Fig.…”
Section: Fig 4 Colocalization Of B-glyc-kdel and B-glyc-kdelgl Withmentioning
confidence: 56%
See 1 more Smart Citation
“…A number of the protein toxins are produced by bacteria and are important for severe diseases caused by these organisms. This is, for instance, the case for diphtheria toxin, although vaccination of the population has helped to control this disease, and for pseudomonas toxin, tetanus toxin, botulinum toxin, and Shiga toxin [14]. Shiga toxin is not only produced by Shigella dysenteriae, which is the infective agent in dysenteria, but Shiga-like toxins are also produced by E. coli, giving rise to infections and disease and being a serious health problem in several countries [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…L'attachement du pentamère de sous-unités B induit l'entrée de la sous-unité A dans la cellule [128]. La toxine est internalisée par voie endocytosique et les vésicules formées, contenant la toxine, fusionnent avec des lysosomes.…”
Section: Arrêt De La Synthèse Protéiqueunclassified